Inflamed adipose tissue: A culprit underlying obesity and heart failure with preserved ejection fraction - Li, Chenyu; Qin, Donglu; Hu, Jiarui; Yang, Yang; Hu, Die; Yu, Bilian (Frontiers in Immunology, 2022)
The incidence of heart failure with preserved ejection fraction is increasing in patients with obesity, diabetes, hypertension, and in the aging population. However, there is a lack of adequate clinical treatment. Patients with obesity-related heart failure with preserved ejection fraction display unique pathophysiological and phenotypic characteristics, suggesting that obesity could be one of its specific phenotypes. There has been an increasing recognition that overnutrition in obesity causes adipose tissue expansion and local and systemic inflammation, which consequently exacerbates cardiac remodeling and leads to the development of obese heart failure with preserved ejection fraction. Furthermore, overnutrition leads to cellular metabolic reprogramming and activates inflammatory signaling cascades in various cardiac cells, thereby promoting maladaptive cardiac remodeling. Growing evidence indicates that the innate immune response pathway from the NLRP3 inflammasome, to interleukin-1 to interleukin-6, is involved in the generation of obesity-related systemic inflammation and heart failure with preserved ejection fraction. This review established the existence of obese heart failure with preserved ejection fraction based on structural and functional changes, elaborated the inflammation mechanisms of obese heart failure with preserved ejection fraction, proposed that NLRP3 inflammasome activation may play an important role in adiposity-induced inflammation, and summarized the potential therapeutic approaches.